Acute Hepatic Porphyria – Minireview - Aida SAVU; Andrei EDU; Lucian NEGREANU (Modern Medicine)
Acute Hepatic Porphyria (AHP) is an uncommon and hereditary illness that belongs to a group of disorders known as porphyries. This condition results from a deficiency of the porphobilinogen deaminase enzyme, which plays a role in heme production, a crucial component of haemoglobin in the bloodstream. This deficiency leads to the accumulation of substances called porphyrins in the body, which can trigger the appearance of severe and potentially life-threatening symptoms. In the following, we will discuss classifications - with a focus on the similarities and differences between subtypes of porphyria, the pathophysiology of acute hepatic porphyria, risk factors – and their influence on the onset of the disease, clinical manifestations, diagnosis, and management – both curative and symptomatic, all of which play a very important role in understanding this rare condition.